NUTRITIONAL ANTHROPOMETRY OF TRIBAL ADOLESCENT GIRLS USING Z SCORES: ITS ASSOCIATION WITH SOCIOECONOMIC STATUS - Meenakshi Surpande,; Rekha Sharma, (The Bioscan, 2026)
The tribal societies in India are undisputedly considered to be the weakest sections of the population in terms of common socioeconomic and socio-demographic factors such as poverty, illiteracy, lack of developmental facilities, lack of adequate primary health facilities etc. The present investigation was undertaken to study the nutritional status of tribal adolescent girls through anthropometry. In all 387 tribal adolescent girls (13 to 18 years old) were purposively selected from four Ashram shalas of tribals located at Higna, Ramtek, Deolapar and Navegaon taluka places of Nagpur District. The anthropometric measurements viz., height and weight were recorded using standard procedures. BMI was computed, compared and classified according to WHO (2007) standards. The Z scores of height, weight and BMI were computed and classified according to the Indian Academy of Paediatrics (IAP) 2015 Standards. The results of the study showed that according to the height Z score classification, 91.99% of girls were normal, 6.46% were stunted and 1.55% were severely stunted. As per the Weight Z Score classification, 96.90 % of girls were normal, 2.84% were wasted and 0.26 % were severely wasted. The BMI Z classification showed 90.44 % normal whereas 0.78%, 2.33%, 5.94% and 0.52% as severe underweight, underweight, overweight and obese respectively. The statistical analysis did not show any association between the z scores and age groups of the adolescent girls (p>0.05). It can be concluded that intervention programmes based on nutrition awareness among tribal adolescent girls may help to achieve the SDG goals for zero hunger. Keywords Nutritional anthropometry, Height Z Score, Weight Z Score, BMI Z Score, Kuppuswamy Socioeconomic Status